2003
DOI: 10.1056/nejmoa022657
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Long-Term Cabergoline Therapy for Tumoral and Nontumoral Hyperprolactinemia

Abstract: Cabergoline can be safely withdrawn in patients with normalized prolactin levels and no evidence of tumor. However, because the length of follow-up in our study was insufficient to rule out a delayed increase in the size of the tumor, we suggest that patients be closely monitored, particularly those with macroprolactinomas, in whom renewed growth of the tumor may compromise vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
3
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(173 citation statements)
references
References 42 publications
7
152
3
11
Order By: Relevance
“…The results obtained by our group and those discussed here seem to suggest that long-lasting dopaminergic agonists can be useful in the management of ACTH-secreting adenomas, in addition to other hormone-secreting adenomas and non-functioning pituitary tumors already known to be sensitive to such drugs [26, 27, 28, 29, 30]. …”
Section: Discussionmentioning
confidence: 67%
“…The results obtained by our group and those discussed here seem to suggest that long-lasting dopaminergic agonists can be useful in the management of ACTH-secreting adenomas, in addition to other hormone-secreting adenomas and non-functioning pituitary tumors already known to be sensitive to such drugs [26, 27, 28, 29, 30]. …”
Section: Discussionmentioning
confidence: 67%
“…Therefore, being able to discontinue SA in some patients with acromegaly, analogous to the situation in patients with prolactinomas treated with DA (14,15), is an attractive theoretical possibility. Based on the observations mentioned above, we hypothesized that in a subset of patients with acromegaly who respond extremely well to SA, as reflected by an excellent biochemical control with relatively low doses, such agents may cause irreversible functional changes in GH release and might therefore be stopped after several years of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to note that studies have shown that pregnancy induces remission of hyperprolactinemia in two-thirds of women after discontinuation of DA (76-100% with non-tumoral hyperprolactinemia, 66-70% with microprolactinomas, 64-70% with macroprolactinomas). Although the exact mechanism is still unclear, it was hypothesized that autoinfarction of the tumour might be the reason for remission [88][89].…”
Section: Management Of Prolactinomas In Pregnancymentioning
confidence: 99%